Performance Analysis of SMES Integrated with Offshore Wind Farms to Power Systems through MT-HVDC - Mohammed A. Badr; Ahmed M. Atallah; Mona A. Bayoumi (Institute of Advanced Engineering and Science, 2016)
With the increase in the development of offshore wind farm (OWF) around the world, this paper describes OWF consisting of permanent magnet synchronous generator (PMSG) wind turbines connected to Active network (AC grid) and Passive network (loads) through Multi Terminal High voltage direct current(MT-HVDC) transmission system. This paper discusses the effect of using a Superconducting Magnetic Energy Storage (SMES) unit in a hybrid power system that contains OWF. In this paper, we have aggregated 300 wind turbines of 1.5 MW PMSG using an aggregation technique (multi full aggregated model using equivalent wind speed (MFAM_EWS)). Furthermore, we have used a detector to detect any tripping of any wind turbine and substitute the shortage of power due to this loss of wind turbines immediately through SMES. The Active network in this paper should have a minimum of 150 MW power to be supplied by controlling the SMES unit (absorbing or providing power according to the system requirement). Simulation has been carried out by MATLAB/Simulink program to test the effectiveness of the SMES unit during tripping some of the wind turbines, fluctuation in wind speeds, load change and voltage dips.